Comparative Analysis Of Phraseological Units In Uzbekistan And English - Uktamova, Mokhigul; Bahodirova, Madinabonu (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article analyzes common phraseological units in Uzbek and English, highlighting similarities and differences in meaning and use. The main attention is paid to the difficulties that arise in the process of translating phraseological units from one language to another and issues of lexical equivalence. The results of the study serve to deepen understanding of both languages ​​and reveal important aspects of interlingual phraseology.